Mid‐lateral approach for revascularization of an amputated second toe: A case report - Ken Nishimura; Katsuyasu Fukasawa; Runa Sugawara; Koichi Kobayashi (Clinical Case Reports)
Abstract The plantar or dorsal approach has been previously reported for the replantation or revascularization of a completely or incompletely amputated lesser toe. However, no reports exist describing an alternative approach for the replantation or revascularization of an amputated lesser toe, either complete or incomplete. We encountered a rare case of revascularization of an incompletely amputated second toe using a mid‐lateral approach. The purpose of this case report was to describe the mid‐lateral approach, which is novel in its nature for the replantation or revascularization of a completely or incompletely amputated lesser toe. A 43‐year‐old male was involved in a motor vehicle accident and had incomplete crush amputation of a second toe at the base of the nail, along with open dislocation of the distal interphalangeal (DIP) joint in the third toe. We performed artery‐only revascularization of the second toe using a mid‐lateral approach, with the patient in the supine position with his hip in flexion and external rotation. The postoperative course was uneventful, and the second toe was deemed viable. The Japanese Society for Surgery of the Foot (JSSF) standard rating system of the lesser toe was rated 90 and the Self‐Administered Foot Evaluation Questionnaire (SAFE‐Q) scored 100 in all the mentioned categories. The mid‐lateral approach could be an option for the replantation or revascularization of an amputated lesser toe distal to the proximal interphalangeal (PIP) joint.